Case Fatality Rates of Recurrent Thromboembolism and Bleeding in Patients Receiving Direct Oral Anticoagulants for the Initial and Extended Treatment of Venous Thromboembolism: A Systematic Review. (September 2015) - Gómez-Outes, Antonio; Lecumberri, Ramón; Suárez-Gea, M. Luisa; Terleira-Fernández, Ana-Isabel; Monreal, Manuel; Vargas-Castrillón, Emilio
Background: In patients with venous thromboembolism (VTE), the study of the case fatality rate (CFR) of VTE recurrences and bleeding complications may be of help to balance the risks and benefits of anticoagulant therapy. Objective: To investigate the CFR with the direct oral anticoagulants (DOACs; dabigatran, rivaroxaban, apixaban, and edoxaban) in patients with VTE. Methods: We conducted a systematic review and meta-analysis of randomized clinical trials testing the DOACs versus standard initial treatment of VTE (parenteral anticoagulant for ≥5 days plus vitamin K antagonists [VKAs] for ≥3 months) and DOACs versus placebo or VKA for extended treatment. Two investigators independently extracted the data. A random effects meta-analysis was conducted using StatsDirect software. Results: Overall, 10 trials in 35 029 patients were included. During initial treatment, the rate of recurrent VTE per 100 patient-years (%/yr) and CFR (%) was similar in patients receiving DOACs or standard therapy (4.1%/yr vs 4.4%/yr; P = .21 and 16% vs 13%; P = .61, respectively). However, major bleeding (1.8%/yr vs 3.1%/yr; P = .003), fatal bleeding (0.1%/yr vs 0.3%/yr; P = .02), and CFR (6% vs 10%; P = .18) were lower with DOACs than with standard therapy. During extended treatment, both all-cause mortality and recurrent VTE per 100 patient-years were lower with DOACs than with placebo (0.6%/yr vs 1.1%/yr; P = .01 and 1.9%/yr vs 10.9%/yr; P < .0001, respectively), but there were no statistical differences between treatments on CFR of VTE recurrences ( P = .17). No fatal bleeding events were reported during extended treatment. Conclusion: The use of DOACs was associated with fewer major and fatal bleedings and corresponding CFR than standard initial treatment of VTE, and fewer recurrent VTEs and mortality than placebo during extended therapy, although the CFR of recurrent VTE was not reduced.